Colossians and Philemon - Martin, Ralph Philip (London, UK Oliphants, 1978)
Includes bibliographical references and indexes.
First published 1974.
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries